ChemInform Abstract: A Simple and Stereoselective Synthesis of (Z)‐1, 2‐Bis‐arylselanyl Alkenes from Alkynes Using KF/Al2O3. Issue 19 (18th April 2013) - Lara, Renata G.; Rosa, Paloma C.; Soares, Liane K.; Silva, Marcio S.; Jacob, Raquel G.; Perin, Gelson
Abstract However, the reaction of phenylacetylene with dimesityl diselenide only provides the alkynyl selenide (IV).